Congenital myotonic dystrophy: Detrusor muscle involvement in a child - Mundada, Vivek B.; Hildebrandt, Torsten (Journal of Pediatric Neurology, 2011)
We report a child with congenital myotonic dystrophy who presented at the age of 28 mo with marked smooth muscle involvement of the urinary tract in the form of myotonia of detrusor muscle. Congenital myotonic dystrophy is a multi-system disorder affecting skeletal, smooth and cardiac muscles. Smooth muscle involvement predominantly affects the gastrointestinal tract. Involvement of the urogenital smooth muscles causing disturbances of micturition are extremely rare and has so far only reported in adult cases. There is little published on the effects of myotonia on the detrusor muscle affecting micturition. The involvement of the urinary system in the previously published cases was based upon history of symptoms alone and flowmetry, cystometry, and/or sphincter electromyography were normal in them. To our knowledge there have been no previous reports of CDM1 causing renal tract involvement with abnormal bladder function leading to hydronephrosis in children.
Keywords: Congenital myotonic dystrophy; smooth muscles; urinary tract pathology